2019
DOI: 10.3390/pr7010026
|View full text |Cite
|
Sign up to set email alerts
|

Modeling/Simulation of the Dividing Wall Column by Using the Rigorous Model

Abstract: Dividing wall column (DWC) is an atypical distillation column with an internal, vertical WE partition wall that effectively accommodates two conventional distillation columns into one to improve the thermodynamic efficiency. In previous studies, different equivalent models by combining conventional columns are adopted to approximate the DWC modeling, which may not well describe the integration of the DWC; moreover, the computational cost increases when multiple columns are implemented to represent one DWC. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Since constructing such diagrams requires the design of each alternative at numerous different values of the feed composition and other variables, most engineers have used shortcut design methods such as assuming constant relative volatility and constant molar overflow and using the vapor rate or total energy consumption as an objective function. Furthermore, when comparing alternatives to the conventional direct and indirect sequences, most authors reported that DWCs provide cost savings. However, most do not considered the possibility of stacking the two conventional columns, i.e., adjusting the column pressures so that direct heat transfer between the condenser of one column and the reboiler of the other column is possible. …”
Section: Introductionmentioning
confidence: 99%
“…Since constructing such diagrams requires the design of each alternative at numerous different values of the feed composition and other variables, most engineers have used shortcut design methods such as assuming constant relative volatility and constant molar overflow and using the vapor rate or total energy consumption as an objective function. Furthermore, when comparing alternatives to the conventional direct and indirect sequences, most authors reported that DWCs provide cost savings. However, most do not considered the possibility of stacking the two conventional columns, i.e., adjusting the column pressures so that direct heat transfer between the condenser of one column and the reboiler of the other column is possible. …”
Section: Introductionmentioning
confidence: 99%
“…For increasingly complex industrial technologies, Gao and Dai [26][27][28] proposed the fault detection and diagnosis (FDD) and data-driven approaches in the modeling, control, and optimization of complex industrial systems. Many design variables are involved in the chemical distillation industry, so commercial software, such as Aspen Plus, can better design, optimize, and control the distillation process [29,30]. Aspen Plus (Aspen Tech, Bedford, MA, USA) is a large-scale general process simulation system for plant design, steady-state design, and dynamic simulation.…”
Section: Introductionmentioning
confidence: 99%